Adverse events following adenovirus type 4 and type 7 vaccine, live, oral in the Vaccine Adverse Event Reporting System (VAERS), United States, October 2011–July 2018. Issue 44 (16th October 2019) - McNeil, Michael M.; Paradowska-Stankiewicz, Iwona; Miller, Elaine R.; Marquez, Paige L.; Seshadri, Srihari; Collins, Limone C.; Cano, Maria V.
Abstract: Background: In March 2011, the U.S. Food and Drug Administration licensed adenovirus type 4 and type 7 vaccine, live, oral (Barr Labs, Inc.) (adenovirus vaccine) for use in military personnel 17 through 50 years of age. The vaccine was first universally administered to U.S. military recruits in October 2011. We investigated adverse event (AE) reports following the adenovirus vaccine submitted to the Vaccine Adverse Event Reporting System (VAERS). Methods: We searched the VAERS database for U.S. reports among persons who received adenovirus vaccine during October 2011 through July 2018 including participants in a military observational study. We reviewed all serious reports and accompanying medical records. We compared the proportion of serious reports in a proxy military recruit population and reviewed all reports of suspected allergic reactions following adenovirus vaccination. Results: During the analytic period, VAERS received 100 reports following adenovirus vaccination; 39 (39%) were classified as serious and of these, 17 (44%) were from the observational study. One death was reported. Males accounted for 72% of reports. Median age of vaccinees was 19 years (range 17–32). The most frequently reported serious AEs were Guillain Barré syndrome (GBS) (n = 12) and anaphylaxis (n = 8); of these, two GBS and all the anaphylaxis reports were reported in the observational study. Reports documented concurrent receipt of multiple other vaccines (95%) and penicillin G (IM Pen G) or other antibiotics (50%). Conclusions: The reporting rate for serious AEs was higher than with other vaccines administered in the comparison military recruit population (39% vs 18%); however, we identified no unexpected or concerning pattern of adenovirus vaccine AEs. Co-administration of vaccines and IM Pen G was commonly reported in this military population. These exposures may have contributed to the GBS and anaphylaxis outcomes observed with the adenovirus vaccine. Future adenovirus vaccine safety studies in a population without these co-administrations would be helpful in clarifying the vaccine's safety profile.